Description of Colonoscopy and Histopathology of Chronic Diarrhea Causes in Non-Neoplasm: Literature Review - Afifah Sakdyyah; Muhammad Begawan Bestari; Sri Suryanti (The Indonesian Society for Digestive Endoscopy, 2021)
Chronic diarrhea is a diarrhea symptom which persists for ≥ 4 weeks as a symptom of a disease. Chronic diarrhea is a symptom which often becomes the patient’s cause to be referred to gastroenterology. In general, the prevalence of chronic diarrhea is approximated to be 5% in each populations, but there are obstacles in diagnosing the cause of chronic diarrhea, due to many differential diagnoses of the cause of chronic diarrhea. The cause of chronic diarrhea could be neoplasm and non-neoplasm. In several studies, through results of colonoscopy and histopathology, it was found that the most common cause of chronic diarrhea was non-neoplasm, including IBD, microscopic colitis as a risk factor, and infectious colitis as a differential diagnosis. Each of those diseases has similar symptoms, but different pathological description. Through descriptions of colonoscopy and histopathology of chronic diarrhea causes, it is possible to differentiate each non-neoplasm causes of chronic diarrhea. It could facilitate in finding the differences among the causes of chronic diarrhea especially in non-neoplasm cases, therefore possibly establishing a definite diagnosis.